Culture –Specific Coping and Quality of Life among Ghanaians Living with Chronic Illness: Mental Illness and Chronic Kidney Disease - Anang, H. B. A. (University of Ghana, 2014)
The study examined culture-specific coping and quality of life among Ghanaians living with chronic illness such as mental illness and chronic kidney disease. A sample size of 150 was used comprising of 50 mentally ill patients, 50 Chronic Kidney Disease patients and 50 healthy controls. Participants were sampled from the Accra Psychiatric Hospitals, Pantang General Hospital and the Korle-Bu teaching Hospitals respectively. The concurrent mixed method design was used which comprised a cross-sectional survey for the quantitative and a semi-structured interview which comprised the qualitative. Patients were administered with the Africultural Coping Systems Inventory), the General Health Questionnaire WHO Quality of life Brief (WHOQOL) and a semi- structured interview also based on the Africultrual Systems Inventory was also generated).Results showed that there was a significant positive relationship between culture specific coping and quality of life generally.. Also there was a significant negative relationship between the General Health Status of Patients and the quality of life of patients. The results further revealed that, type of condition has a significant effect on Cognitive Emotional Coping and Spiritual Centred Coping. However, no significant differences were found in Collective Coping and Ritual Centered. Results showed that the type of condition has a statistically significant effect on the overall health-related quality of life. The type of condition also has statistically significant effects on the Physical Psychological and Social domains but not on Environmental.
Thesis (Mphil) - University of Ghana, 2014